2009
DOI: 10.1128/ec.00037-09
|View full text |Cite
|
Sign up to set email alerts
|

Altering Sphingolipid Metabolism in Saccharomyces cerevisiae Cells Lacking the Amphiphysin Ortholog Rvs161 Reinitiates Sugar Transporter Endocytosis

Abstract: Amphiphysins are proteins thought to be involved in synaptic vesicle endocytosis. Amphiphysins share a common BAR domain, which can sense and/or bend membranes, and this function is believed to be essential for endocytosis. Saccharomyces cerevisiae cells lacking the amphiphysin ortholog Rvs161 are inviable when starved for glucose. Altering sphingolipid levels in rvs161 cells remediates this defect, but how lipid changes suppress remains to be elucidated. Here, we show that the sugar starvation-induced death o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Sphingolipids are required for endocytosis (Zanolari et al , 2000), and previous work has suggested their functional association with Rvs proteins (Desfarges et al , 1993; Balguerie et al , 2002; Germann et al , 2005; McCourt et al , 2009; Morgan et al , 2009). To further examine the functional relationship of Rvs proteins with sphingolipids, we asked whether changes in levels of complex sphingolipids affected either the fitness of BAR domain mutants or Rvs167-GFP localization.…”
Section: Resultsmentioning
confidence: 99%
“…Sphingolipids are required for endocytosis (Zanolari et al , 2000), and previous work has suggested their functional association with Rvs proteins (Desfarges et al , 1993; Balguerie et al , 2002; Germann et al , 2005; McCourt et al , 2009; Morgan et al , 2009). To further examine the functional relationship of Rvs proteins with sphingolipids, we asked whether changes in levels of complex sphingolipids affected either the fitness of BAR domain mutants or Rvs167-GFP localization.…”
Section: Resultsmentioning
confidence: 99%
“…Endophilins recruit dynamin and deform membranes and thus have essential roles in membrane curvature sensing and remodeling (8). Mutation of several genes in sphingolipid biosynthesis can also suppress endocytic defects resulting from deletion of RVS genes (6), and aberrant regulation of membrane sphingolipids interfered with their functions (7). A plasma membrane quantitative genetic interaction map further validated the links of eisosomes, protein-based structures that generate invaginations at the plasma membrane, with sphingolipid metabolism and endosomal trafficking (9).…”
mentioning
confidence: 92%
“…Although the balance between cholesterol and sphingolipids within the plasma membrane has long been implicated in endocytic membrane trafficking (4,5), in contrast to cholesterol functions, little is still known about the roles of sphingolipids. However, genetic studies in yeast have suggested a functional link between sphingolipid metabolism and the endophilin homologs RVS161 and RVS167, which are Bin/Amphiphysin/Rvs (N-BAR) 3 domain-containing endocytic proteins (6,7). Endophilins recruit dynamin and deform membranes and thus have essential roles in membrane curvature sensing and remodeling (8).…”
mentioning
confidence: 99%
“…RVS161 and RVS167, and their metazoan homologues amphiphysin and endophilin, coordinate constriction of endocytic necks with other events required for the endocytic reaction 17 21 . Forward genetic screens for suppressors of rvs161 or rvs167 mutants identified mutations in enzymes of sphingolipid metabolism 22 , 23 . Subsequently, large-scale epistatic miniarray profile (E-MAP) studies extended these results by identifying additional enzymes of both sphingolipid and ergosterol metabolism that genetically interact with N-BAR proteins 24 .…”
Section: Introductionmentioning
confidence: 99%